IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KABUPATEN KAMPAR NO 5 TAHUN 2009 TENTANG PENEMPATAN TENAGA KERJA LOKAL (STUDI KASUS PT. RAMAJAYA PRAMUKTI) - Muhammad Hasnan Nusainu; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The issue regarding the implementation of local government policy of Kampar Regency is due to the rapid of job demand to the work world of the society as the field could not cover it all. The problems following the issue emerged as many of companies did not notify the job vacancy to the Social and Labor Affairs and make no priority to the local labors; the Official did not have information about the availability of job vacancy and could not control the placement of the local labors at those companies. As this implementation of the policy undertaken to the industrial society properly, it is intended that the society of Kampar Regency can manage their own revenue and increase the prosperity of environment particularly to the local inhabitants. The objective of this research is to find out how the implementation of local government policy no 5 year 2009 about the provision of local labor is. This kind of research is descriptive design precisely quantitative method with triangulation check and cross check to the given responses of the informants. The result of this research indicates that the implementation of local government policy no 5 year 2009 about the provision of local labor in Kampar Regency has not yet been implemented extensively. Based on the research finding, the factors affected this kind of policy are the lack of communication, resource, disposition, and structured-bureaucracy.Keywords: Policy, Implementation, Local Labor, Local Government Rules